STRATEGY OF SPECIAL LIBRARY IN INCREASING THE AVAILABILITY OF LIBRARY COLLECTIONS - Fitriani, Fitriani; Rohani, Laila (PERSPEKTIF: Journal of Social and Library Science, 2023)
This research discusses the strategies carried out by the Medan district court office library in increasing the availability of their collections in order to realize their vision and mission which includes fostering, developing and maintaining library materials in the special library. This research uses a descriptive qualitative method by describing, describing and describing the data and then analyzing the research results obtained from the field. The purpose of this research is to determine the strategy of special libraries in the Medan district court library in their efforts to increase the availability of collections that can be utilized by users. There were 3 informants in the research, consisting of administrative staff and the finance department who were also responsible for library management, then library management staff and library guards. The results of the research show that the library managers who manage the special library at the Medan district court office are not those from the library science department, causing a lack of special and in-depth attention to the library collections in the library. Even so, the strategy they use to increase the availability of collections is to maximize the budget as best as possible by adding collections related to law and also adding several collections other than that, such as collections of history books and biographies.